2018
DOI: 10.1061/(asce)st.1943-541x.0002092
|View full text |Cite
|
Sign up to set email alerts
|

Fragility Analysis of Space Reinforced Concrete Frame Structures with Structural Irregularity in Plan

Abstract: Because significant damages to structures having structural irregularity in their plans were repeatedly observed during many past earthquakes, there have been great research efforts to evaluate their seismic vulnerability. Although most of the previous studies used simplified structural representations such as one-dimensional or two-dimensional models in the fragility analysis of plan-irregular structures, simple analytical models could not represent true seismic behavior from the complicated nonlinear couplin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…To account for uncertainty in the seismic damage states of bridges, seismic fragility curves are introduced. Seismic fragility is defined as the conditional probability that the demand of a structure exceeds a specified threshold for a given earthquake intensity [40][41][42], and seismic fragility curves are often used for setting retrofit and repair priorities of bridges after an unexpected and disastrous event [43]. In this study, SA, which can be calculated by the GMPE provided in equation 4, is introduced as the earthquake intensity.…”
Section: Target Bridge Transportation Networkmentioning
confidence: 99%
“…To account for uncertainty in the seismic damage states of bridges, seismic fragility curves are introduced. Seismic fragility is defined as the conditional probability that the demand of a structure exceeds a specified threshold for a given earthquake intensity [40][41][42], and seismic fragility curves are often used for setting retrofit and repair priorities of bridges after an unexpected and disastrous event [43]. In this study, SA, which can be calculated by the GMPE provided in equation 4, is introduced as the earthquake intensity.…”
Section: Target Bridge Transportation Networkmentioning
confidence: 99%
“…The analysis results of these studies showed that earthquake damages to structures varied with different ground motion properties. In addition, for an accurate seismic fragility analysis of structures, numerous studies on seismic fragility assessments using analytical models [3][4][5][6][7][8][9][10] have utilized real ground motion records from world-wide well-known earthquakes. However, these records may not reflect the characteristics of a specific region.…”
Section: Mathematical Problems In Engineeringmentioning
confidence: 99%
“…In addition, earthquakes have frequently occurred in the southeastern part of Korea in recent years, exposing these many industrial complexes to seismic hazards. Thus, the importance of structural risk assessment has become increasingly important, and there have been continuous efforts to mitigate earthquake damages using seismic fragility analyses [3,4]. This study concentrates on the structural fragility of liquid storage tanks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences between two parts of the country were markedly observed. Moon, et al [12] employed a fragility approach to investigate the effect of plan structural irregularity and confirmed that the more irregular the structures, the higher the risk they pose. Meanwhile, the effect of the soilstructure interaction on the fragility curves was investigated by Anvarsamarin, et al [13] with the finding that adopting the average spectral acceleration (S a.avg ) intensity measure is more efficient in capturing the effect of the inherent uncertainties of strong ground motions on the structural response parameters.…”
Section: Introductionmentioning
confidence: 98%